Contributions of Design Thinking to Project Management in an Innovation Context. Issue 2 (April 2016) - Ben Mahmoud‐Jouini, Sihem; Midler, Christophe; Silberzahn, Philippe
ABSTRACT: Researchers have long recognized that standard approaches to project management are ill‐suited to address changes in the environment or business needs, particularly in innovative contexts characterized by uncertainty and complexity. Instead of being concerned with the efficient implementation of a deliberate strategy, a project in such a context becomes a process for strategy formulation. Three imperatives for project management arise as a result: managing the explorative phase, managing the involvement of stakeholders in the project, and managing the project in relation to the strategizing process of the firm. We propose that design thinking, a recent evolution in the field of design, can make some important contributions to these imperatives. Design thinking has been highlighted by practitioners as well as academia as a novel methodology that is potentially valuable for improving innovative outcomes, whether they are products, services, or strategies. We examine and articulate these possible contributions through 10 propositions that could form an agenda for future experimentation and empirical research on innovation project management.